2014
DOI: 10.5539/jel.v3n4p96
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Outdoor School Ground Lessons on Students’ Science Process Skills and Scientific Curiosity

Abstract: The purpose of this study was to investigate the effects of outdoor school ground lessons on Year Five students' science process skills and scientific curiosity. A quasi-experimental design was employed in this study. The participants in the study were divided into two groups, one subjected to the experimental treatment, defined as "eco-hunt" group and the other had no experimental treatment, defined as control group. This study used intact four classes which consisted of 119 students and randomly assigned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 24 publications
2
22
0
5
Order By: Relevance
“…The increasing scores trend reflected the process skill development of students taught using multiple intelligence-based learning. Active learning activities, conducted outside the classroom by implementing discovery strategy, led to good development of process skills aspects (Ting & Siew, 2014;Sen & Vekli, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The increasing scores trend reflected the process skill development of students taught using multiple intelligence-based learning. Active learning activities, conducted outside the classroom by implementing discovery strategy, led to good development of process skills aspects (Ting & Siew, 2014;Sen & Vekli, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Students can use the environment as a learning resource. Lin Ting (2014) revealed that the ability to observe can be increased by expanding the process of instructional learning outside the classroom; hence it can provide opportunities to see, touch, feel, smell and hear that requires the use of all senses. This opinion was supported by the results of a study from Sugiyono (2017) which stated that science learning with the outdoor learning method proved effective in improving the quality of learning.…”
Section: A Formation Of Color In Soap Bubbles B the Riverbed Whose mentioning
confidence: 99%
“…Follow-up comparisons on the dimensions of science process skills and scientific curiosity were analysed and discussed. The findings of this study will provide a framework for science ISSN 1948-5476 2017 teachers to teach students through interesting and meaningful outdoor activities' (Ting & Siew, 2014). Then, this is so because the teaching and learning that is only based on theory and textbooks will cause difficulties for students to practice their knowledge in the field.…”
Section: Student Teaching and Learning Processmentioning
confidence: 86%